Is It Culture or Is It Language? Examine the Language Effects in Cross-Cultural Research on Categorization. [article] . - Ji, Li-Jun.
Differences in reasoning styles between Chinese and European Americans held even when controlling for the language of testing. Bilingual Chines organized objects in a more relational and less categorical way tha European Americans, whether tested in English or in Chines, Thus, cukture affects categorization independent of the testing language. Nevertheless, language affected some Chines bilinguals' categorization. The responses of Chinese from the Mainland and Taiwan were more relational when tested in Chinese than when tested in English. Responses of Chinese from Hongkong and Singapore were equally relational when tested in Chinese and English. Age oand context of learning of English are discussed to explain the differential language effects among different Chinese groups. Theoretical and methodological implications are discussed. -- (from the author)
Keywords: Psychology-Periodicals.